Kesenjangan Implementasi Pasal 16 UU Nomor 2 Tahun 2022 tentang Jalan dalam Perspektif Siyasah Tanfidziyyah - Dwi Rozalia; Relit Nur Edi; Nur Rahmah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The condition of road infrastructure in Abung Tinggi District, North Lampung Regency, reflects a significant gap between legal provisions and on the ground realities. Under Law Number 2 of 2022 concerning Roads, particularly Article 16, local governments are mandated to organize and manage road infrastructure within their authority. This study aims to analyze the implementation of Article 16 in road management in Abung Tinggi District and to examine it from the perspective of siyasah tanfidziyyah. This research employs an empirical juridical method with a field approach, utilizing data collected through interviews with relevant government agencies and affected communities. The findings indicate that the local government has authority over 215 road segments, totaling 1,205.06 km. The 2026 road management program includes the construction of 15 km of roads and the periodic rehabilitation of 20 km. However, implementation remains suboptimal due to budget constraints, limited resources, and environmental as well as weather-related challenges. From the perspective of siyasah tanfidziyyah, the government, as the executor of public policy, bears responsibility for ensuring public welfare through adequate infrastructure provision. Therefore, improvements in policy implementation are necessary to achieve more effective and equitable road management